Blue's clues & you! Blue's big baking show [videorecording (DVD)] - Dela Cruz, Joshua, 1989- (Paramount Home Entertainment, 2022)
It's a sweet and delicious day at Blue's Bakery as Josh and Blue are baking bibingka, a cake from the Philippines! Next up is a trip to Blue's Bistro, a very fancy restaurant. Then, celebrate birthdays with an incredibly special birthday cake made by Mr. Salt and Mrs. Pepper. And finally, play detective and try to find Mr. Salt₂s missing pies, dun dun dun!